Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1111/j.1399-5618.2006.00300.x
|View full text |Cite
|
Sign up to set email alerts
|

Increased levels of SNAP‐25 and synaptophysin in the dorsolateral prefrontal cortex in bipolar I disorder

Abstract: Changes in SNAP-25 and synaptophysin in BPDI suggest that changes in specific neuronal functions could be linked to the pathology of the disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
50
0
1

Year Published

2007
2007
2012
2012

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(59 citation statements)
references
References 58 publications
8
50
0
1
Order By: Relevance
“…Using quantitative RT-PCR analysis on brain samples, we showed that individuals with 'CC' genotype showed a significant increase in mRNA level of the major isoform of SNAP25 in adult (SNAP25b) in prefrontal cortex. These results are consistent with the significant increase in SNAP25 protein level previously reported in Brodmann's area 9 (dorsolateral prefrontal cortex) in patients with BD, 15 as cellular and animal studies showed that variations in mRNA levels of SNAP25 correspond to equivalent variation in protein levels. 32,33 The SNP4 is located between two AP-1 consensusbinding sequences in a region that contributes to the repression of the SNAP25 transcription by binding of POU4F2 (also called Brn-3b).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Using quantitative RT-PCR analysis on brain samples, we showed that individuals with 'CC' genotype showed a significant increase in mRNA level of the major isoform of SNAP25 in adult (SNAP25b) in prefrontal cortex. These results are consistent with the significant increase in SNAP25 protein level previously reported in Brodmann's area 9 (dorsolateral prefrontal cortex) in patients with BD, 15 as cellular and animal studies showed that variations in mRNA levels of SNAP25 correspond to equivalent variation in protein levels. 32,33 The SNP4 is located between two AP-1 consensusbinding sequences in a region that contributes to the repression of the SNAP25 transcription by binding of POU4F2 (also called Brn-3b).…”
Section: Discussionsupporting
confidence: 92%
“…12,13 Second, postmortem studies have shown modifica-tions of SNAP25 protein levels in some brain regions of bipolar patients. 14,15 Third, SNAP25 gene has been widely associated with attention-deficit hyperactivity disorder (ADHD), which is known to share genetic susceptibility with early-onset BD. [16][17][18] We analysed SNAP25 as a candidate gene for susceptibility to BD and, more specifically, to earlyonset BD.…”
Section: Introductionmentioning
confidence: 99%
“…46 Our third main finding is that our study implicates the process of CME in psychotic disorders by showing altered expression of proteins involved in or regulating this pathway, namely synaptotagmin, heat shock cognate 71-kDa protein, 106 44 These changes are in keeping with studies that found similar changes in the expression of SPTAN1, 45 heat shock cognate 71-kDa protein, 114 cathepsin D, 90 and the clathrin coat assembly protein AP180 in schizophrenia. 49 Findings have not, however, been entirely consistent; for example, dynamin-1 expression changes have been observed in some 45,49,51 but not all 115,116 studies, and changes in dynactin subunit 2 were observed in the opposite direction in a previous proteomic study of the anterior cingulate cortex. 51 Consequently, we focused some of our validation experiments on proteins involved in CME and we confirmed changes in ANXA6, PCMT1, and SPTAN1.…”
Section: Commentmentioning
confidence: 90%
“…It is worth noting that previous expression studies in SCZ and BPD generally reported a tendency towards a reduced expression in SCZ and BPD, 76,77 with increases in some synaptic-associated proteins, such as SNAP-25 60 and conflicting reports regarding other such as GAP-43 and synaptophysin. 37,[78][79][80][81][82] A strength of the current investigation is the use of two complementary proteomic approaches, 2D DIGE and GeLC-MS/MS to identify candidate diseaseassociated proteins within the MM proteome in SCZ and BPD. The use of these methods has allowed us to identify and then to proceed to validate important new disease-associated proteins within a functionally important but low-abundance proteome.…”
Section: Discussionmentioning
confidence: 99%